The 2022 ENCR Recommendations on recording and reporting of urothelial tumours of the urinary tract - Galceran, Jaume; Parada, David; Eden, Michael; Tumino, Rosario; Warren, Anne Yvonne; Martos, Carmen; Neamtiu, Luciana; Visser, Otto; Daubisse-Marliac, Laetitia (Frontiers in Oncology, 2022)
An updated European Network of Cancer registries (ENCR) Recommendations on Recording and Reporting of Urothelial Tumours of the Urinary Tract had been published in 2022. After the publication by the ENCR of the “Recommendations for coding bladder cancers” in 1995, knowledge about the biology and pathology of urinary tract tumors and their classification has varied and increased substantially. On the other hand, several studies have shown that cancer registries use different definitions, criteria for inclusion and coding of urothelial tumors. This great variability among registries affects not only the criteria for recording (registration, coding and classification) but also the criteria of reporting (counting in the statistics of incidence and survival) urinary tract tumors. This causes difficulties in the data comparability from different registries. Recording and reporting of urothelial tumors requires the application of standard criteria that must take into account the combination of the multiple aspects as the primary topography, the histological type, the grade, the extent of invasion, the multi-centricity, the progressions and the time interval between tumors. This led to the creation of a Working Group of the ENCR that developed these recommendations on the recording and reporting of urothelial tumors of the urinary tract. This article reports these recommendations and the rationale for each.